Total area networking ATM, IP, frame relay, and SMDS explained - Atkins, John; Norris, Mark (J. Wiley, 1995)
Total Area Networking ATM,IP, Frame Relay and SMDS Explained Second Edition John Atkins and Mark Norris BT, UK Total Area Networking explains how high-speed communications allow local facilities to become part of a more global network. This concept is the essential basis for super-connectivity, when the user sees a distributed set of network-based resources as one. This fully updated second edition of the highly successful Total Area Networking has been extended to include IP networks and now covers both network technology and its applications. It illustrates the practical implementation of a total area network using the principles developed for Intelligent Networks, Intranets and Virtual Private Networks. * Main topics include ATM (Asynchronous Transfer Mode), IP (Internet Protocol), Frame Relay and SMDS (Switched Multi-magabit Data Service). * Covers the whole spectrum of communications technology, from theory to implementation. * Provides a clear understanding of what new technology can do and how it can best be deployed. * Allows the non-expert to question both accurately and indepth. Essential reading for a wide ranging audience, including professionals involved in the planning and implementation of information systems, undergraduate and postgraduate students of computer science, electrical engineering and telecommunications.